Renin–angiotensin system gene polymorphisms and endometrial cancer. Issue 3 (May 2016) - Pringle, Kirsty G; Delforce, Sarah J; Wang, Yu; Ashton, Katie A; Proietto, Anthony; Otton, Geoffrey; Blackwell, C Caroline; Scott, Rodney J; Lumbers, Eugenie R
Abstract : Endometrial cancer (EC) is the most common gynaecological malignancy and its incidence is increasing. Dysregulation of the endometrial renin–angiotensin system (RAS) could predispose to EC; therefore, we studied the prevalence of RAS single nucleotide polymorphisms (SNPs) in Australian women with EC. SNPs assessed were AGT M235T (rs699); AGTR1 A1166C (rs5186); ACE A240T and T93C (rs4291, rs4292) and ATP6AP2 (rs2968915). They were identified using TaqMan SNP Genotyping Assays. The C allele of the AGTR1 SNP (rs5186) was more prevalent in women with EC (odds ratio (OR) 1.7, 95% confidence interval (CI) (1.2–2.3), P =0.002). The CC genotype of this SNP is associated with upregulation of the angiotensin II type 1 receptor (AGTR1). The G allele of AGT rs699, which is associated with higher angiotensinogen (AGT) levels, was less prevalent in women with EC (OR 0.54, 95% CI (0.39–0.74), P <0.001) compared with controls. AGT and AGT formed by removal of angiotensin I (des(Ang I)AGT) are both anti-angiogenic. In women with EC who had had hormone replacement therapy (HRT), the prevalence of the AGTR1 SNP (rs5186) and the ACE SNPs (rs4291 and rs4292) was greater than in women who had no record of HRT; SNP rs4291 is associated with increased plasma ACE activity. These data suggest there is an interaction between genotype, oestrogen replacement therapy and EC. In conclusion, the prevalence of two SNPs that enhance RAS activity was different in women with EC compared with healthy controls. These genetic factors may interact with obesity and hyperoestrogenism, predisposing ageing, obese women to EC.